The Construction Action Programme of the International Labour Office – A View of On-going Implementation and Implications for Research - Werna, Edmundo (Penerbit Universiti Sains Malaysia, 2006)
The paper focuses on the Construction Action Programme, that is an initiative in progress of the International Labour Office. Such a programme is important as it provides a platform of social dialogue at the national level to discuss problems and to propose solutions related to labour in the construction industry, leading to the implementation of concrete activities. The process of social dialogue involves the main national representatives of workers, employers and government agencies with a stake in construction. Considering that so far the Construction Action Programme is known only within limited circles, the paper contributes to the understanding of construction in developing countries by disseminating information about it. It provides a comprehensive view of the programme, ranging from its planning phase up to the present stage of implementation. At the same time, the paper also presents a research agenda derived from the experience of the programme, and concludes with inferences on possible synergies between research and development assistance in construction in developing countries.